Piling European practice and worldwide trends : proceedings of a conference organized by the Institution of Civil Engineers, and held in London on 7-9 April 1992 - Sands, M. J. (Thomas Telford, 1992)
This title from Thomas Telford contains the proceedings of a conference organised by the Institution of Civil Engineers, and held in London on 7-9 April 1992.
Keywords: Piling (Civil engineering) -- Congresses.; elektronické knihy; electronic books